Analysis of Electronic Medical Record Security Aspects in Maintaining Patient Data Confidentiality at Hospital X in Bandung City - Sri Rahayu; Sali Setiatin (International Journal of Psychology and Health Science, 2025)
The implementation of the Electronic Medical Record (EMR) system at Hospital X is a strategic step to enhance the efficiency and quality of healthcare services. This study aims to evaluate data security aspects of the EMR system, focusing on access security, data integrity, and system availability. A descriptive qualitative method was used to explore patient data protection practices. The results indicate that the hospital has implemented role-based access control, audit trails, and user activity monitoring. However, several shortcomings were identified, such as the absence of a regular password change policy, lack of two-factor authentication, and infrequent system security testing. In terms of availability, the system is supported by 24-hour vendor services, although technical challenges such as network disruptions and hardware limitations remain. This study recommends strengthening security policies, conducting regular staff training, and improving technological infrastructure to ensure optimal patient data protection and service effectiveness.